The Relationship Between Peer Social Support and Student Academic Resilience - Frischa Meivilona Yendi; Feby Najmah Khairiyah; Firman Firman; Dina Sukma (Jurnal Neo Konseling, 2023)
Academic resilience is a form of student resilience in stressful conditions, a way to rise from adversity, adapt, and how to solve problems to face various existing academic demands. One of the factors that influence academic resilience is social support. This study was conducted to examine the significant relationship between peer social support and student academic resilience. This type of research is quantitative with a descriptive correlational approach with a sample of 176 students taken using the Proportional Random Sampling technique. The results showed that there was a significant positive relationship between peer social support and student academic resilience of the Islamic Religious Education Study Program, Faculty of Social Sciences, Universitas Negeri Padang. Thus, the higher the peer social support, the higher the student academic resilience of the Islamic Religious Education Study Program, Faculty of Social Sciences, Universitas Negeri Padang. Vice versa, the lower the peer social support, the lower the student academic resilience of the Islamic Religious Education Study Program, Faculty of Social Sciences, Universitas Negeri Padang.